Somatosensory Gating Is Modulated by Anodal Transcranial Direct Current Stimulation - Montoro, Casandra I.; Winterholler, Christine; Terrasa, Juan L.; Montoya, Pedro (Frontiers in Neuroscience, 2021)
Background: Anodal tDCS of the somatosensory cortex causes cerebral hyperexcitability and a significant enhancement in pain thresholds and tactile spatial acuity. Sensory gating is a brain mechanism to suppress irrelevant incoming inputs, which is elicited by presenting pairs of identical stimuli (S1 and S2) within short time intervals between stimuli (e.g. 500 ms). Objectives/Hypothesis: The present study addressed the question of whether tDCS could modulate the brain correlates of this inhibitory mechanism. Methods: Forty-one healthy individuals aged 18 to 26 years participated in the study and were randomly assigned to tDCS (n = 21) or SHAM (n = 20). Somatosensory evoked potentials (SEP) elicited by S1 and S2 pneumatic stimuli (duration of 100ms, ISI 550 ± 50ms) and applied to the index finger of the dominant hand were recorded before and after tDCS. Results: Before the intervention, the second tactile stimuli significantly attenuated the amplitudes of P50, N100 and the late positive complex (LPC, mean amplitude in the time window 150-350) compared to the first stimuli. This confirmed that sensory gating is a widespread brain inhibitory mechanism that can affect early- and middle-latency components of SEPs. Furthermore, our data revealed that this response attenuation or sensory gating (computed as S1 minus S2) was improved after tDCS for LPC, while no changes were found in participants who received SHAM. Conclusion: All these findings suggested that anodal tDCS might modulate brain excitabillity leading to an enhancement of inhibitory mechanisms elicited in response to repetitive somatosensory stimuli during late stages of information processing.